Comparison of laboratorial tests for the diagnosis of human T-lymphotropic virus type 1 (HTLV-1) and type 2 (HTLV-2) in HIV-1 infected patients - Campos, Karoline Rodrigues (2015)
The present study aimed at investigating the best algorithm definition to be employed for diagnosing the human T lymphotropic virus type 1 (HTLV-1) and type 2 (HTLV-2) in HIV-1 infected/Aids patients. Blood samples of 1,608 HIV-1 infected patients from the AIDS Reference Center (CRT DST/AIDS-SP) were tested for the presence of HTLV-1/2 antibodies using two screening assays (EIA Murex HTLV-I+II, and Gold ELISA HTLV-I/II), and confirmed by two Blots [HTLV Blot 2.4 (Western Blot –WB) and INNO-LIA HTLV I/II (Line ImmunoAssay - LIA)], and one molecular assay (pol real-time PCR). The screening tests detected 51(Murex) and 49 (Gold ELISA) reagents sera. WB , confirmed 23 HTLV-1, 12 HTLV-2, six HTLV, and nine showed HTLV indeterminate profiles. LIA confirmed 24 HTLV-1, 20 HTLV-2, and six HTLV. PCR detected 18 HTLV-1- and 12 HTLV-2-infected blood samples. By using any confirmatory assay, 50 patients confirmed HTLV infection: 25 HTLV-1 (1.55 %), 21 HTLV-2 (1.31 %) and four HTLV (0.25 %). The sensitivity of LIA, WB and PCR assays were 96 %, 76 % and 60 %, respectively. By considering the assays cost as the sole variable, the best testing algorithm for diagnosing HIV-1/HTLV-coinfection in HIV-1 infected patient was the use of PCR followed by LIA technique.